SOCIAL IMPACTS OF TOURISM INDUSTRY CAUSED BY AGRICULTURAL LAND USE CHANGE IN TOURISM INFRASTRUCTURE DEVELOPMENT IN UBUD REGION, GIANYAR REGENCY, PROVINCE OF BALI, INDONESIA - Roy Anggriawan Pratama; Arief Rosyidie (ASEAN Journal on Hospitality and Tourism, 2017)
This research wants to identify the impact of tourism activity on agricultural land use changes in Ubud, Gianyar, Bali. Components of this study consists of four main elements, namely the development of tourism activities in Ubud, physical development that occurs as a result of tourism activities, the spatial pattern of agricultural land use changes that occur as a result of their physical development related to the tourism sector and the impacts that comes from agricultural land use change in Ubud. Tourism industry in Ubud give two different impacts on the society, in on one hand they give a benefit to some people, especially to people who have their business in tourism industry, but in other hand, tourism activities give negative impacts for those who do not live in tourism industry. So in this research, it will identify what is the impact on the social side and why this condition is happening.